SPREADING OF NORTH PACIFIC WATER IN THE SEA OF OKHOTSK - Gladyshev S.V.; Khen G.V. (My University, 2004)
The water mass spreading observed in the study region suggests the following conclusions. First, the Kruzenshtern Strait represents a stable source of the NPW for the Sea of Okhotsk and only small SOW quantities can enter through it into the ocean. Second, the stability of the NPW position in the strait points to the existence of a relatively strong and steady current, which transports the NPW water to the Sea of Okhotsk. In this situation, tidal mixing can transform the thermohaline properties of the NPW only insignificantly. Third , we believe that it is precisely this current that is responsible for the formation of temperature and oxygen extremums in the Sea of Okhotsk, because it transports the least transformed NPW in the density interval corresponding to these extremums.